THE ASSESSMENT ON ESP WRITING FOR FISHERY DEPARTMENT STUDENTS - Theresia Widihartanti (UAD TEFL International Conference)
The application of ESP for college students is very crucial since they are led to have skills that are apt with the needs of working environment. The learning using ESP method must be implemented using the well-designed assessment that will encourage fishery students to have high self-esteem to explore their experience in fishery world. To what extends that the assessment will be appropriate for the writing papers of fishery students? The research method used was classroom action research to elevate students’ ideas and observation research that was conducted in the field since the activities conducted needed a series of events. There were some findings: 1) An apt topic had to be chosen; 2) An experience learned that supported the data; 3) The result of the series of activities that was reported; and 4) The application of scoring rubric based on the previous activities that assessed the final writing papers. The fishery department students as the subject of the research was in their fourth semester since they had to learned prior knowledge needed in fishery field.